Ranking and Closest Element Algorithms on Centralized Diamond Architecture - Damrudi, Masumeh; Jadidy Aval, Kamal (International Journal of Engineering and Technology, 2018)
Employing an appropriate algorithm, hardware and technique makes operations easier and faster in today digital world. Searching data which is a fundamental operation in computer science is an important problem in different Areas. An efficient algorithm is useful to search a data element in huge amount of data while information is growing in every second. There are various papers on searching algorithms to find data elements whereas different types of query in different areas of works including position, rank, count and closest element exists. Each of these queries may be useful in different computations. This paper proposed two algorithms of these four types of query employing Centralized Diamond architecture which consume constant execution time.Â Â